Politik pemberdayaan kelompok tani sawit swadaya di Kampung Sialang Palas, kecamatan Lubuk Dalam, Siak - Khairul Anwar; Adianto Adianto (Unri Conference Series: Community Engagement, 2020)
This service activity is set in the context of Sialang Palas Village, Lubuk Dalam District, Siak Regency. This area consists of 90% of oil palm plantations but land-use patterns, information and communication technology, decreased purchasing power of farmers, low nutritional status of farmer households. Meanwhile, the influence of local leadership is getting weaker, and Gapoktan institutions are not functioning. In this condition, there was a change in the political behavior of peasants which was initially critical, dynamic, and weakened, eroded by the narrower structure of the local democratic space, and the impact of changes in the national political economy. Therefore, farmer participation in group management needs to be increased. This activity aims to increase the capacity of independent smallholders in managing farmer groups and making decisions through the application of "my palm oil:" and a model of political empowerment. This activity was carried out in Sialang Palas Village, Lubuk Dalam, Siak Regency, and this service took the theme "Community Empowerment in the New-Normal Era". The problem is how to increase the capacity of poktan farmers in decision making and group management in Sialang Palas? The methods used are: First, preparation and socialization of the program to Karya Bersama farmer groups in Sialang Palas Village. Second, conducting lectures and discussing materials (1) leadership; (2) group management; (3) decision-making process; (4) strategic issues; (5) processing local potential (3) discussing the model of "empowerment politics" and issues of development and governance in Lubuk Dalam; (6) Village Assistance and Assistance. The results of the community service activities include: First, published scientific articles. Second, video activities and knowledge about group decision making. Third, knowledge and skills in processing palm oil waste and knowledge about family nutrition.